1989
DOI: 10.1111/j.1432-1033.1989.tb14612.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the microenvironment on the kinetic properties of immobilized enzymes

Abstract: A new immobilization method was developed in order to perform a systematic study of the influence of the microenvironment on the properties of immobilized enzymes. The enzyme, alcohol dehydrogenase, was first activated, then polypeptide arms of known composition were quantitatively grafted and finally the enzyme was covalently immobilized by co-polymerization of the activated ends of the peptide arms with acrylamide monomers. In this way, the polypeptide linker arms fully determine the properties of the microc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…BCCP-FL (71 kDa compared to the exclusion limit of 4 Â 10 6 Da) can be immobilized inside the agarose beads. Bille et al studied the diffusional constraints imposed by the solid matrix on immobilized yeast alcohol dehydrogenase and found that the kinetic properties of the immobilized enzyme are solid matrix-dependent (27). Concentration gradients of substrates are likely to be developed along the radius of the bead (high at the surface, low at the centre) due to diffusion limits imposed by the solid matrix.…”
Section: Kinetic Constants Of Bccp-flmentioning
confidence: 99%
“…BCCP-FL (71 kDa compared to the exclusion limit of 4 Â 10 6 Da) can be immobilized inside the agarose beads. Bille et al studied the diffusional constraints imposed by the solid matrix on immobilized yeast alcohol dehydrogenase and found that the kinetic properties of the immobilized enzyme are solid matrix-dependent (27). Concentration gradients of substrates are likely to be developed along the radius of the bead (high at the surface, low at the centre) due to diffusion limits imposed by the solid matrix.…”
Section: Kinetic Constants Of Bccp-flmentioning
confidence: 99%
“…Diffusion is also an important step for heterogeneous reactions occurring at the solid surface. Limitation of substrate diffusion towards the enzyme adsorbed on the soil surface could be one of the key factors for the decrease in enzyme activity (Arrio-Dupont and Béchet, 1989;Bille et al, 1989;Douzou and Petsko, 1984;Konecny and Voser, 1977). Enzyme substrate reactions are zero order kinetic.…”
Section: Substrate Diffusionmentioning
confidence: 99%
“…The concentration of the substrate remains lowest adjacent to the surface relative to the bulk of the solution. The concentration gradient develops from the bulk of the solution to the soil surface (Bille et al, 1989;Ku and Lentrichia, 1989). There can be three different situations if the diffusion is: slow, equal and fast relative to substrate consumption at the soil surface.…”
Section: Substrate Diffusionmentioning
confidence: 99%
“…However, covalent linkage requires the modification of one or both parties which may also affect the biological activity. In many cases, these methods give rise to high enzyme loadings maintaining the native structure and biological activity, even increasing the response of the adsorbed enzymes compared to the activity in solution [13][14][15]. However, none of these methods can control the orientation of the enzyme on the solid substrates, the other key factor that determines the enzyme performance in terms of active site accessibility.…”
Section: Introductionmentioning
confidence: 99%